Securing software by enforcing data-flow integrity - Castro, Miguel; Costa, Manuel; Harris, Tim (Symposium on Operating Systems Design and Implementation (OSDI), 2006)
Software attacks often subvert the intended data-flow in a vulnerable program. For example, attackers exploit buffer overflows and format string vulnerabilities to write data to unintended locations. We present a simple technique that prevents these attacks by enforcing data-flow integrity. It computes a data-flow graph using static analysis, and it instruments the program to ensure that the flow of data at runtime is allowed by the data-flow graph. We describe an efficient implementation of data-flow integrity enforcement that uses static analysis to reduce the instrumentation overhead. This implementation can be used in practice to detect a broad class of attacks and errors because it can be applied automatically to C and C++ programs without modifications, it does not have false positives, and it has low overhead.